MENINGKATKAN KEMAMPUAN MEMBACA MELALUI MEDIA TUBOKAS PADA PESERTA DIDIK KELAS III SDN 44 HOLONTHALANGI KOTA GORONTALO - Timbowo, Afriani Putri; Pulukadang, Wiwy Triyanty; Monoarfa, Fidyawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research problem statement is whether using Tubokas media can enhance the reading ability of Grade III students at SDN 44 Hulontanglangi, Gorontalo City? This study aims to improve students’ reading ability using Tubokas media in Grade III at SDN 44 Hulontalangi, Gorontalo City. This research employs a classroom action research (CAR) design. Data collection techniques include observation, tests, and documentation. The research findings indicate that the reading ability of Grade III students at SDN 44 Hulonthalangi, Gorontalo City, reached 10 students who can read (50%) and 10 students who cannot (50%). During the implementation of cycle I, in the first meeting, the reading ability was shown by 9 students as good (46.25%), in the second meeting of cycle I, it increased ti 11 students (52.5%), and in the tirdh meeting of the cycle I, it further increased to 13 students (63.75%). Subsequently, in the cycle II, students’ reading ability improved to 17 students (88.75%). Therefore, it can be concluded that the reading ability of Grade III students at SDN 44 Hulonthalangi, Gorontalo City, has improved